Feasibility assessment of double-blind, crossover, randomized controlled trial protocol comparing two oxygen-supplemented pulmonary rehabilitation for patients with chronic obstructive pulmonary disease: A pilot study - Akihiro Ito; Akane Morito; Masahiro Ishizaka; Yukihiro Ogawa; Yuki Kawai; Yuta Hanawa; Naotaka Onodera; Yoshiaki Endo; Isato Fukushi; Kotaro Takeda; Taichi Mochizuki; Yasushi Inoue; et al. (PLoS ONE, 2026)
Background Pulmonary rehabilitation (PR) for patients with chronic obstructive pulmonary disease (COPD) improves exercise tolerance and COPD assessment test score (CAT). Oxygen supplementation during PR facilitates exercise physiological benefits. This study aimed to assess the feasibility of a trial comparing two oxygen supplementation methods, with the hypothesis that both would be effective and produce distinct outcomes. Methods This double-blind, crossover, randomized controlled trial compared two PR programs—Program A (including PR under FiO₂ 0.3) and Program B (including PR under FiO₂ 0.5)—using high-flow nasal cannula oxygen therapy in patients with COPD and exertional dyspnea (n = 6). Data on the 6-minute walk distance (6MWD), CAT, muscle strength, body composition analysis, respiratory function, and joint range of motion were collected. Participants underwent one month of regular PR followed by two months of oxygen-supplemented PR, with data collected again after this period. Statistical significance was set at 0.05 with a power of 0.8, and the required sample size was calculated accordingly. Results The required sample size could not be calculated based on the 6MWD. The improvement in CAT by Program A was greater than that by Program B. The improvements in muscle parameters by Program B were greater than those by Program A. The standardized effect size and the corresponding required sample sizes for the CAT, quadriceps muscle power, lower leg circumference, trunk muscle mass, and leg muscle mass were 0.32/81, 0.66/8, 0.17/114, 0.27/88, and 0.24/56, respectively. Conclusions Given the small number of participants, the 6MWD and CAT were not appropriate primary endpoints for comparing the effectiveness of the two oxygen supplementations during PR in patients with COPD. However, the quadriceps muscle power was identified as the most suitable primary endpoint among all the investigated parameters.